OPTIMASI PARAMETER BUKAAN DAN PENGAKU DIAGONAL PADA BALOK KASTELA YANG TERTUMPU LATERAL - Sanjaya, Erwin; Suryoatmono, Bambang (Jurnal Ilmiah Teknik Sipil; Jurnal Ilmiah Teknik Sipil, Vol. 24, No. 1, Januari 2020DO - 10.24843/JITS.2020.v24.i01.p05, 2020)
S hear force in general greatly contributes to cause failure of castellated beams so  diagonal stiffeners on the openings are required. Optimization was done by vary dimension of openings and diagonal stiffeners . Finite element method is utilized to perform nonlinear analysis. The objective of this research is to compare the numerical results of castellated beams without diagonal stiffeners with AISC design procedures that provided in Steel Design Guide 31, AISC 2016. Furthermore, nonlinear behaviour that involves critical load and Von Mises stress distribution of castellated beams with and without diagonal stiffeners were studied to obtain optimum dimension of openings and diagonal stiffeners. Optimum value in this research involves the greatest initial stiffness (K i ), strength (w max ), and ductility ( m ) of structure. The results showed that AISC design procedures could predict the location of maximum stress accurately and yield more conservative ultimate strength of beam compared to numerical result. The optimum models on castellated steel beams without diagonal stiffeners are CB60-1 ( w nstmax = 56,16 kN/m) and CB45-1 ( m nst = 3,06) with average initial stiffener 5,78 kN/m. While, the o ptimum models on castellated steel beams with diagonal stiffeners are CB45-33 (K sti = 6,99 kN/m/m), CB60-11 (w stmax = 67,53 kN/m), and CB60-24 ( m st = 2,79). Thus, utilization of d i agonal stiffeners is effective to increase initial stiffness and strength of structure, but reduce the structure’s ductility.